The impact of post-sales factors on customer-oriented business performance of fast-moving consumer goods enterprises in Ho Chi Minh City - Hoang , Cuu Long; Pham , Thi Phuong Dung; Nguyen , Phuc Khanh (Journal of Finance - Marketing Research, 2025)
This study aims to assess the impact of post-sales factors on the customer-oriented business performance of fast-moving consumer goods (FMCG) enterprises in Ho Chi Minh City. In the context of increasing competition and rapidly changing consumer trends, post-sales activities such as product experience, after-sales services, customer care, complaint handling, customer communities, and long-term value commitment play a crucial role in maintaining customer satisfaction, loyalty, and revenue growth. The research adopts a mixed-method approach, combining qualitative and quantitative methods, with a structural equation modeling (SEM) framework to examine the relationships among the studied variables. Data were collected from 222 FMCG enterprise managers and 279 consumers in Ho Chi Minh City from June to December 2024 through online and offline surveys. The findings indicate that after-sales services play important roles in reducing customer attrition and customer communities drive revenue growth. The significant effects of product experience on customer satisfaction and loyalty; after-sales service only impact on customer satisfaction not loyalty. FMCG enterprises in Ho Chi Minh City should prioritize enhancing product experience and after-sales services while fostering personalized customer engagement to strengthen loyalty and long-term brand commitment.